New Concept of Onco-Hypertension and Future Perspectives. Issue 1 (January 2021) - Kidoguchi, Satoshi; Sugano, Naoki; Tokudome, Gorou; Yokoo, Takashi; Yano, Yuichiro; Hatake, Kiyohiko; Nishiyama, Akira
Abstract : Owing to aging populations, the prevalence of hypertension and associated cardiovascular events has been increasing worldwide. The morbidity and mortality due to cancer have also been increasing with aging populations. Several small-molecule inhibitors have been used in cancer therapy, which have a positive impact on the prognosis and survival of patients with cancer. Consequently, the number of cancer survivors with hypertension has been rapidly increasing. Anticancer therapy, including vascular endothelial growth factor inhibitors, increases blood pressure. However, both clinical and laboratory evidence are lacking regarding optimal blood pressure control in patients with hypertension with cancer. Here, we propose the concept of onco-hypertension, which is an evolving subspecialty focused on the complex pathophysiology of hypertension and cancer. In this review, we highlight blood pressure changes in cancer, hypertension induced by anticancer therapy, and optimal blood pressure management in patients with hypertension with cancer. In addition, we discuss needed studies to further establish this new onco-hypertension concept.